Real-Time Fuel Consumption Monitoring System Integrated With Internet Of Things (IOT) - Hapsari, Adella Winanda; Prastowo, Hari; Pitana, Trika (Department of Naval Architecture - Diponegoro University, 2021)
Fuel is an important aspect in the operation of ships that require high costs. The high cost of fuel is not followed by an automatic fuel monitoring process. By not using the fuel consumption monitoring method that works automatically, the shipping management does not know for sure the ship's fuel consumption is in accordance with the shipping mileage, thus triggering fraud committed by the ship's crew against the ship's fuel. Fuel consumption monitoring is carried out primarily to identify opportunities to improve energy efficiency and reduce costs. By following technological developments, Internet of Things (IoT) technology has begun to be applied in various industrial fields because it can transmit data in real-time via the internet network without human-to-human or human-to-computer interaction. In this research, the design of models and experiments related to a monitoring system for fuel consumption was carried out using sensors and microcontrollers integrated with the internet to obtain accurate and real-time data. The test results show that the volume of fuel available in the tank, the volume of fuel discharged, the flow rate of fuel, and the location of the system can be known by the user in real-time via the IoT website. Based on the results of measurements using an ultrasonic level sensor, it is known that the measurement results are quite accurate with a deviation of Â± 0.5 cm. Meanwhile, the measurement results by the flow sensor are less accurate because the fuel flow only relies on the force of gravity.